Consultative study : Shenzhen in 2008 - a potential electronics manufacturing hub? - Ho, Melina Ken Yi. (2008)
In 1976, under the open-door policy, Shenzhen was established as a SEZ to attract FDI and technology transfer. Today, Shenzhen plays a major role in the electronics sector of China. Its electronic industry output accounted for 15% of the country’s industry output. Shenzhen has passed the stage of basic industrialization, and is now in the phase of restructuring to high value added industries.